Research and application of hydraulic fracturing borehole bag sealing technology. Issue 2 (May 2021) - Zhou, Dongping; Wang, Xuanlin; Guo, Chenye; Zhou, Junjie; Wang, Kai
Abstract: Aiming at the problems existing in the sealing of fracturing boreholes using the regular bag sealing device in the conventional 'two sealing and one injection' process, this paper investigated a practical and reliable ZBQ-30/1.0 modified pneumatic grouting pump for coal mines, optimized the 'B' sealing material which was applied for the sealing of fracturing boreholes designed the 'three sealing and two injection' hole sealing device which was applied for the sealing of hydraulic fracturing boreholes, and finally carried out in Songzao Coal Mine. The results showed that the strength of the optimized 'B' sealing material was 14.64~15.43MPa, which was much higher than that of the regular extraction expansion sealing material. In addition, the hydraulic fracturing could withstand more than 20MPa, and the sealability was also well. This research implied the fixed-point sealing of hydraulic fracturing drilling can be carried out to save the sealing cost.